Protective effect of an aqueous extract of Harpagophytum procumbens upon Escherichia coli strains submitted to the lethal action of stannous chloride - Almeida, M. C.; Soares, S. F; Abreu, P. R. C; Jesus, L. M; Brito, L. C; Bernardo-Filho, M. (Cellular and Molecular Biology, 2007)
Regardless of its lethal effects upon Escherichia coli (E. coli) cultures trough the production of free radicals (FR), stannous chloride (SnCl2) remains to be the most used reducing agent on the production of technetium-99m radiopharmaceuticals, to obtain images on nuclear medicine. Moreover, authors have reported that vegetal extracts are able to protect Escherichia coli cultures against the cytotoxicity of this agent. Harpagophytum procumbens, also known as Devil’s Claw, is a plant used in folk medicine, as an analgesic and anti-inflammatory in cases of joint and back pain, on the treatment of degenerative rheumatoid arthritis, osteoarthritis, kidney inflammation and heart diseases. The presence of this extract reduced the lesive effects of SnCl2 upon E. coli AB1157 (proficient in DNA repair), BW9091 (deficient in the xthA gene) and BH110 (deficient in the xthA, nfo and fpg genes) cultures, and the deficient strains (BW9091 e BH110) were more sensible to this SnCl2 action than the proficient one. The substances in the extract could be acting as: (i) chelator of the stannous ions, avoiding the generation of FR, (ii) FR scavenger, protecting the cells against the oxidation, and/or (iii) an oxidant compound acting upon the stannous ions, reducing the SnCl2 cytotoxicity.